Advertisement Remove all ads

Solve: (3"X" - 2)/4 - ("2x" + 3)/3 = 2/3 - "X" - Mathematics

Sum

Solve: `(3"x" - 2)/4 - ("2x" + 3)/3 = 2/3 - "x"`

Advertisement Remove all ads

Solution

`(3"x" - 2)/4 - ("2x" + 3)/3 = 2/3 - "x"`


`= (3"x" - 2)/4 - ("2x" + 3)/3 = 2/3 - "x"/1`


`= (3(3"x" - 2) - 4(2"x" + 3))/12= (2 xx1)/(3 xx 1) - ("x" xx 3)/(1 xx 3)`

 

`=(9"x" - 6 - "8x" - 12)/12 = (2 - "3x")/3`

`= ("x" - 18)/12 = (2 - "3x")/3`

= 3(x - 18) = 12(2 - 3x)

= 3x - 54 = 24 - 36x

= 3x + 36x = 24 + 54

= 39x = 78

`"x" = 78/39 = 2`

∴ x = 2

Concept: Solving Linear Inequations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (C) | Q 1.07 | Page 169
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×